Reflecting film with good surface smoothness and high reflectivity and preparation method thereof

By using a combination of modified incompatible resin and inorganic particles in the middle layer of the reflective film, and using longitudinal and transverse stretching processes to form a cell structure, the unevenness and thermal wrinkle of the film surface are solved, and high reflectivity and smoothness are achieved Its reflective film is suitable for large-size LCD backlight modules and panel lamps.

CN119116511AInactive Publication Date: 2024-12-13HEFEI LUCKY SCIENCE & TECHNOLOGY INDUSTRY COMPANY LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411150542.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-21
Publication Date
2024-12-13
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

In large-size backlight modules and panel lamps, the light reflection uniformity is reduced due to film surface unevenness, and the thermal wrinkle problem has not been effectively solved, which affects the use effect.

Method used

A three-layer structure reflective film design, in which the intermediate layer uses a combination of modified incompatible resin and inorganic particles to form a cell structure through longitudinal and transverse tensile processes, which improves the lateral elastic modulus and reflectivity of the film, and controls it. Process parameters eliminate internal stress and ensure the flatness of the film surface.

Benefits of technology

It realizes a reflective film with good surface flatness and high reflectivity. It is suitable for large-size LCD backlight modules and panel lamps. The reflectivity reaches more than 95.0%. There is no heat wrinkle or wave curl after baking, which significantly improves the use effect of the film. .

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119116511A_ABST
    Figure CN119116511A_ABST
Patent Text Reader

Abstract

The reflecting film with good surface smoothness and high reflectivity is of a three-layer structure and comprises an ABA structure or an ABC structure, and an intermediate layer of the reflecting film comprises the following components in percentage by weight: 5-45% of inorganic particle a master batch, 24-45% of incompatible resin master batch, 0.1% of a nucleating agent, 0.1% of a flexibilizer a, 0.1% of a dispersing agent and 9.7-70.7% of polyester. The reflecting film prepared by the invention has good film surface smoothness and high reflectivity, and is especially suitable for large-size LCD backlight modules and panel lamps.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a reflective film, in particular to a reflective film with good surface flatness and high reflectivity and a preparation method thereof. Background Art

[0002] Currently, reflective films are commonly used in LCD display backlight modules, mini-LEDs, mobile phones, and panel lights. These films are typically placed at the bottom layer of the module to reflect light emitted by LEDs, thereby increasing LED lamp utilization and reducing energy consumption. Reflective films used in large-size backlight modules and panel lights require very high surface flatness. Poor surface flatness reduces the uniformity of light reflection, especially for edge-entry LCD backlight modules, as there is a risk of scratching the light guide plate. Generally, films have low transverse modulus and poor deformation resistance. Stress release is incomplete, and during secondary processing, stress release causes dimensional changes in the film, resulting in uneven film surfaces. Currently, the film surface unevenness caused by heat wrinkling has not been effectively addressed in the market. After baking or coating, the unevenness worsens, making it very unsuitable for downstream customers. Summary of the Invention

[0003] In order to overcome the drawbacks of the prior art, the present invention provides a reflective film with good surface flatness and high reflectivity and a preparation method thereof. The prepared reflective film has good film surface flatness and high reflectivity, and is particularly suitable for large-size LCD backlight modules and panel lights.

[0004] The technical solution adopted by the present invention to solve its technical problem is: A reflective film with good surface flatness and high reflectivity, wherein the reflective film has a three-layer structure, including an ABA structure or an ABC structure, and the middle layer of the reflective film includes the following components in the following weight percentages: Inorganic particle a masterbatch 5-45% Incompatible resin masterbatch 24-45% Nucleating agent 0.1% Toughener a 0.1% Dispersant 0.1% Polyester 9.7- 70.7%.

[0005] The above-mentioned reflective film has good surface flatness and high reflectivity, and the incompatible resin masterbatch is obtained by blending, modifying and granulating an incompatible resin with Al2O3 particles. The incompatible resin masterbatch includes 30% incompatible resin, 1% Al2O3 and 69% polyester, and the above percentages are weight percentages; the incompatible resin is one or a combination of two of polymethylpentene (TPX), styrene, polypropylene, polyurethane resin, and polycarbonate resin.

[0006] The incompatible resin masterbatch is preferably a polymethylpentene (TPX) masterbatch, produced by adding 1% Al2O3, 30% TPX, and 69% polyester to a vented twin-screw pelletizer. The above percentages are by weight. The polyurethane resin masterbatch is modified with Al2O3, which has a particle size of 100-300nm. Nano-Al2O3 has a large specific surface area and can be well loaded onto the surface of TPX particles. Al2O3 also acts as an inorganic nucleating agent, promoting TPX crystallization during transverse stretch heat setting. Al2O3 itself has excellent high-temperature resistance, and loading it onto the TPX surface improves its heat resistance, preventing cell collapse during transverse stretch setting.

[0007] The synthesis method of styrene masterbatch, polypropylene masterbatch and polycarbonate resin masterbatch is the same as the preparation method of polymethylpentene (TPX) masterbatch.

[0008] Due to TPX's low density and low thermal conductivity, tailing and sticking often occur during granulation, resulting in uneven particle size. This can cause material jamming during film production, impacting feed stability, leading to unstable pressure and thickness fluctuations. Therefore, the incompatible resin TPX is first blended and modified with the inorganic Al2O3 particle to improve thermal conductivity and temperature resistance. This allows for rapid cooling during granulation, facilitating pelletizing and creating a TPX masterbatch. Films made from this modified TPX masterbatch are then biaxially stretched to form pores. During transverse stretching and heat setting, the incompatible resin resists deformation, resulting in a regular, non-collapsed pore shape and improved reflectivity.

[0009] The incompatible resin masterbatch is also a thermoplastic polyurethane plastic masterbatch, which is prepared by adding 1% Al2O3, 30% thermoplastic polyurethane plastic particles (Covestro, model 380A) particles and 69% polyester into a vented twin-screw pelletizer. The above percentages are weight percentages.

[0010] The above-mentioned reflective film has good surface flatness and high reflectivity, and the inorganic particle a masterbatch is inorganic particle a grafted with MAH maleic anhydride grafted SEBS model (FG1901) to make a masterbatch, which includes 60% inorganic particle a, 4% MAH maleic anhydride grafted SEBS and 36% polyester, and the inorganic particle a includes one or two of barium sulfate, titanium dioxide and aluminum oxide.

[0011] In the reflective film having good surface flatness and high reflectivity, the inorganic particles a are preferably titanium dioxide, and further are rutile titanium dioxide.

[0012] The reflective film with good surface flatness and high reflectivity is preferably an ABA structure, and the surface layer includes the following components in percentage by weight: Inorganic particles b 1~3%; Toughener b 0.1%; Antistatic agent 2%; Polyester 94.9~96.9%.

[0013] In the reflective film with good surface flatness and high reflectivity, the inorganic particles b include one or a combination of two of silicon dioxide, titanium dioxide, calcium carbonate, and aluminum oxide.

[0014] The reflective film has good surface flatness and high reflectivity. The toughening agent a contained in the middle layer of the reflective film is a non-crystalline polyester, preferably a combination of PETG:TPEE in a ratio of 1:1; the nucleating agent can be an inorganic nucleating agent or an organic nucleating agent, and the inorganic nucleating agent includes a metal oxide, an inorganic salt, or a clay, and the inorganic nucleating agent includes an organic sodium salt or an aromatic hydroxysulfonate; the nucleating agent is preferably an organic sodium phosphate; the dispersant is preferably polyethylene glycol; the toughening agent b contained in the surface layer of the reflective film is a non-crystalline polyester, such as TPEE; and the antistatic agent is octadecyl dimethyl hydroxyethyl quaternary ammonium nitrate.

[0015] The reflective film with good surface flatness and high reflectivity, wherein the polyester includes one or two of polyethylene terephthalate (PET), polybutylene terephthalate (PBT), and polyethylene naphthalate.

[0016] For the reflective film with excellent surface smoothness and high reflectivity, when the polyester in the middle layer is PET, the incompatible resin is polymethylpentene, and its melt index (MFR) satisfies the requirement of 100 ≤ MFR (260°C, 5kg) ≤ 180 g / min. A too low melt index results in slow TPX flow and easy delamination from PET during melting. A too high melt index results in low TPX molecular weight, poor temperature resistance, and easy cell collapse during horizontal stretching.

[0017] A method for preparing a reflective film with good surface flatness and high reflectivity, the method comprising the following steps: S1, casting sheet: adopt three-layer co-extrusion process; melt and extrude PET polyester chips, antistatic agent, inorganic particles b and toughening agent b in the surface layer, and then introduce them into the mouth of T-die through filter; at the same time, melt and extrude PET polyester chips, inorganic particle a masterbatch, incompatible resin masterbatch, nucleating agent, toughening agent a and dispersant in the middle layer, and then introduce them into the mouth of T-die through filter; then carry out three-layer co-extrusion, the extrusion temperature is controlled at 260-275℃, the vacuum pressure is ≤5KPa, and the molten sheet is cooled by cold roller to obtain casting sheet; S2, stretching film: the casting sheet obtained in step S1 is preheated by longitudinal stretching rollers, and then longitudinally stretched under the auxiliary heating of infrared lamps. The longitudinal stretching ratio (L MD) is 3.0-3.7, and a single-stretch membrane is obtained; the membrane is introduced into the clamps on both sides of the horizontal stretching inlet and clamped, and then enters the horizontal stretching system. The horizontal stretching ratio (L TD ) is 3.2~4.0. After heat setting and cooling, the edges are trimmed in the traction area, and then the film is rolled, slit and packaged to obtain the reflective film.

[0018] The method for preparing the reflective film with good surface flatness and high reflectivity, in step S2, 1.0≤L TD / L MD ≤1.33; total thickness of reflective film is 50-300μm, density of reflective film is 0.65~0.95g / cm 3 .

[0019] The beneficial effects of the present invention are: using modified incompatible resin masterbatch, such as TPX masterbatch, to improve granulation defects, improve the film forming property and stretch ratio of the reflective film, thereby improving the modulus and reflectivity of the reflective film, and improve the heat wrinkle caused by insufficient transverse modulus.

[0020] The reflectivity R of the reflective film prepared by the present invention is 50μm ≥95.0%; R 100μm ≥96.0%; R 150μm ≥96.3%; R 188μm-300μm ≥96.5%.

[0021] The density of the reflective film prepared by the present invention is relatively low, ranging from 0.65 to 0.95 g / cm 3 Before and after baking, the reflective film is flat and has no heat wrinkles or waves, making it very suitable for LCD and panel light industries, and suitable for large sizes. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 Schematic diagram of the ABA layer structure of the reflective film of the present invention.

[0023] In the figure: A, surface layer; B, middle layer; 1, inorganic particle a; 2, incompatible resin; 3, cell; 4, inorganic particle b. DETAILED DESCRIPTION

[0024] The present invention adds an incompatible resin to the intermediate layer of the reflective film. During the preparation of the reflective film of the present invention, the transverse stretching ratio (L TD ) is higher than the longitudinal stretch ratio (L MD ), 1.0≤L TD / L MD ≤1.33, to increase the transverse elastic modulus E of the membrane TD The maximum pressure is 1800~3000MPa, which can improve the thermal wrinkles of the film caused by high temperature baking or coating and improve the flatness of the film surface.

[0025] The three-layer structure of the reflective film of the present invention is preferably an ABA structure, wherein layer A comprises inorganic particles b, toughening agent b, antistatic agent and polyester; layer B comprises inorganic particles a, toughening agent a, dispersant, incompatible resin and polyester.

[0026] The inorganic particles a in layer B may be selected from one or two of barium sulfate, titanium dioxide, and aluminum oxide. Considering the whiteness, shielding properties, refractive index of the inorganic particles and the limitation on the sulfur content in the reflective film, titanium dioxide is preferred.

[0027] The titanium dioxide in layer B is an inorganic substance. Due to compatibility issues, the prepared finished product is prone to dust and debris during subsequent cutting. Therefore, the titanium dioxide is organically modified before granulation to increase its compatibility with polyester.

[0028] Furthermore, rutile titanium dioxide with a particle size of 200nm is used. The Ti-O polarity is high, and a large number of hydroxyl groups are attached to the surface. This can be grafted with maleic anhydride-grafted SEBS (FG1901) to produce titanium dioxide masterbatch. During melt extrusion, the anhydride reacts with the hydroxyl groups on the titanium dioxide surface to form an ester. SEBS is an olefin copolymer, and during the film-making process, SEBS and TPX are well compatible. Specifically, the titanium dioxide masterbatch is prepared by blending, melt-extruding and pelletizing 60% titanium dioxide, 4% MAH maleic anhydride grafted SEBS and 36% polyester in a vented twin-screw pelletizer.

[0029] A nucleating agent is used in the middle layer of the reflective film to increase the crystallization rate of incompatible resins and to increase the transverse elastic modulus of the film during the transverse stretching section. The nucleating agent is preferably sodium organic phosphate, and the amount of nucleating agent added is 0.1% of the weight of the core layer. The above percentages are weight percentages.

[0030] Inorganic particles b are added to the surface of the reflective film to act as an opening agent, improve the uniformity of the film, increase the diffuse reflection of the film, and avoid local halo caused by LED lights during use, thereby affecting the display effect.

[0031] Furthermore, the surface inorganic particles b are preferably silicon dioxide. Considering the uniform light properties of the film surface, the number average particle size of silicon dioxide is best at 3.5 μm, and the added amount accounts for 1-3% of the total weight of the surface layer. The above percentages are weight percentages. By adjusting the content of the surface inorganic particles, reflective films with different glossiness can be prepared, and reflective films with different glossiness can be selected according to different applications.

[0032] Furthermore, the antistatic agent is octadecyl dimethyl hydroxyethyl quaternary ammonium nitrate; the added amount should not be too much, as too much addition will easily accelerate the precipitation of oligomers at the die head and increase the amount, which will easily cause defects such as oligomers on the die head line of the film surface. The added amount of the present invention accounts for 2% of the total weight of the surface layer; the above percentages are weight percentages.

[0033] Furthermore, the surface toughener b of the reflective film is selected from PETG, and the added amount accounts for 0.1% of the weight of the surface layer; the middle layer is a combination of PETG and TPEE in a ratio of 1:1, and the added amount accounts for 0.1% of the weight of the middle layer; the above percentages are weight percentages.

[0034] The preparation method of the reflective film includes: S1, casting sheet: adopting a three-layer co-extrusion process; the PET polyester chips, antistatic agent, inorganic particles b and toughening agent b in the surface layer are melt-extruded and then introduced into the mouth of a T-die through a filter; at the same time, the PET polyester chips, inorganic particle a masterbatch, incompatible resin masterbatch, nucleating agent, toughening agent a and dispersant in the middle layer are melt-extruded and then introduced into the mouth of a T-die through a filter; then the three-layer co-extrusion is carried out, and the obtained molten sheet is cooled by a chill roller to obtain a casting sheet; S2, stretching film: the casting sheet obtained in step S1 is preheated by longitudinal stretching rollers, and then longitudinally stretched under the auxiliary heating of infrared lamps. The longitudinal stretching ratio (L MD ) is 3.0-3.7, and a single-stretch membrane is obtained; the membrane is introduced into the clamps on both sides of the horizontal stretching inlet and clamped, and then enters the horizontal stretching system. The horizontal stretching ratio (L TD ) is 3.2~4.0. After heat setting and cooling, the edges are trimmed in the traction area, and then the film is rolled, slit and packaged to obtain the reflective film.

[0035] During film stretching in step S2, from heat setting to cooling, the track should gradually narrow to control transverse thermal shrinkage. The track shrinkage should be 1-5%, starting from the last heat setting zone and ending in the transition zone. To improve film surface smoothness and eliminate internal stress, the temperature should not drop suddenly from heat setting to cooling. The heat setting zone temperature should be 200-235°C, the transition zone temperature should be 140-180°C, and the cooling zone temperature should be 60-120°C.

[0036] The thickness range of the prepared reflective film is controlled at ≤5%; the thickness range is the difference between the maximum and minimum values ​​measured on the finished roll; the above is the percentage of the total thickness; a large thickness range will cause wave defects on the film surface, bulging edges on the finished roll and other defects. By adjusting the film head opening, stretching ratio, stretching temperature and setting temperature, the thickness range can be controlled within a reasonable range.

[0037] During the modification and granulation process of the inorganic particle a masterbatch and the incompatible resin masterbatch, the added polyester and Al2O3 particles are added separately and are not included in the inorganic particle a and polyester content in the formula.

[0038] The present invention will be further described below with reference to the embodiments.

[0039] Example 1 The reflective film's surface layer comprises 1.0% silica, 0.1% PETG, 2% octadecyldimethylhydroxyethyl quaternary ammonium nitrate, and 96.9% polyester (PET), with the aforementioned percentages representing weight percentages of layer A. The reflective film's middle layer comprises 5% titanium dioxide masterbatch (containing 60% TiO2, 36% polyester PET, and 4% MAH maleic anhydride grafted SEBS), 0.1% PETG and TPEE combination (1:1 ratio), 27% TPX masterbatch (containing 1% Al2O3, 30% TPX, and 69% polyester PET), 0.1% sodium organic phosphate, 0.1% polyethylene glycol, and 67.7% polyester (PET). The longitudinal stretch ratio is 3.6, the transverse stretch ratio is 4.0, and the transverse heat setting temperatures in zones 1-5 are 225 / 225 / 225 / 225 / 205°C, respectively. The transition zone temperature is 160°C, and the cooling zone temperatures are 100 / 70°C. The track shrinkage is 2.5%, and the total thickness of the reflective film is 188μm. The relevant performance table is shown in Table 1.

[0040] Example 2 The surface layer of the reflective film comprises 1.5% silicon dioxide, 0.1% PETG, 2% octadecyl dimethyl hydroxyethyl quaternary ammonium nitrate, and 96.4% polyester PET. The above percentages are the weight percentages of layer A. The middle layer of the reflective film comprises 5% titanium dioxide masterbatch (containing 60% TiO2, 36% polyester PET and 4% MAH maleic anhydride grafted SEBS), 0.1% PETG and TPEE combination (ratio of 1:1), 27% TPX masterbatch (containing 1% Al2O3, 30% TPX and 69% polyester PET), 0.1% sodium organic phosphate, 0.1% polyethylene glycol, and polyester PET 67.7%; longitudinal stretching ratio 3.0, transverse stretching ratio 4.0, transverse stretching heat setting zone 1-5 temperature are 225 / 225 / 225 / 225 / 205℃, the transition zone temperature is 160℃, and the cooling zone temperatures are 100 / 70℃ respectively; the track shrinkage is 2.5%, and the total thickness of the reflective film is 188μm. The relevant performance table is shown in Table 1.

[0041] Example 3 The surface layer of the reflective film contains 2.0% silica, 0.1% toughening agent PETG, 2% octadecyl dimethyl hydroxyethyl quaternary ammonium nitrate, and 95.9% polyester PET. The above percentages are the weight percentages of layer A. The middle layer of the reflective film contains 5% titanium dioxide masterbatch (containing 60% TiO2, 36% polyester PET and 4% MAH maleic anhydride grafted SEBS), 0.1% PETG and TPEE combination (ratio of 1:1), and 27% TPX masterbatch. (Contains 1% Al2O3, 30% TPX and 69% polyester PET), 0.1% sodium organic phosphate, polyethylene glycol 0.1%, polyester PET 67.7%; longitudinal stretching ratio 3.4, transverse stretching ratio 4.0, transverse stretching heat setting zone 1-5 temperatures are 225 / 225 / 225 / 225 / 205℃ respectively, transition zone temperature is 160℃, cooling zone temperature is 100 / 70℃; track shrinkage is 2.5%, total thickness of reflective film is 188μm, relevant performance table is shown in Table 1.

[0042] Example 4 The reflective film's surface layer comprises 3.0% silica, 0.1% PETG, 2% octadecyldimethylhydroxyethyl quaternary ammonium nitrate, and 94.9% polyester (PET), with the aforementioned percentages representing weight percentages of layer A. The reflective film's middle layer comprises 5% titanium dioxide masterbatch (containing 60% TiO2, 36% polyester PET, and 4% MAH maleic anhydride grafted SEBS), 0.1% PETG and TPEE combination (1:1 ratio), 27% TPX masterbatch (containing 1% Al2O3, 30% TPX, and 69% polyester PET), 0.1% sodium organic phosphate, 0.1% polyethylene glycol, and 67.7% polyester (PET). The longitudinal stretch ratio is 3.5, the transverse stretch ratio is 4.0, and the transverse heat setting temperatures in zones 1-5 are 225 / 225 / 225 / 225 / 205°C, respectively. The transition zone temperature is 160°C, and the cooling zone temperatures are 100 / 70°C. The track shrinkage is 2.5%, and the total thickness of the reflective film is 188μm. The relevant performance table is shown in Table 1.

[0043] Example 5 The reflective film's surface layer comprises 1.5% silica, 0.1% PETG, 2% octadecyldimethylhydroxyethyl quaternary ammonium nitrate, and 96.4% polyester (PET), with the aforementioned percentages representing weight percentages of layer A. The reflective film's middle layer comprises 10% titanium dioxide masterbatch (containing 60% TiO2, 36% polyester PET, and 4% MAH maleic anhydride grafted SEBS), 0.1% a 1:1 combination of PETG and TPEE, 27% TPX masterbatch (containing 1% Al2O3, 30% TPX, and 69% polyester PET), 0.1% sodium organic phosphate, 0.1% polyethylene glycol, and 62.7% polyester (PET). The longitudinal stretch ratio is 3.4, the transverse stretch ratio is 3.9, and the transverse heat setting temperatures in zones 1-5 are 225 / 225 / 225 / 225 / 205°C, respectively. The transition zone temperature is 160°C, and the cooling zone temperatures are 100 / 70°C. The track shrinkage is 2.5%, and the total thickness of the reflective film is 188μm. The relevant performance table is shown in Table 1.

[0044] Example 6 The reflective film's surface layer comprises 1.5% silica, 0.1% PETG, 2% octadecyldimethylhydroxyethyl quaternary ammonium nitrate, and 96.4% polyester (PET), with the aforementioned percentages representing weight percentages of layer A. The reflective film's middle layer comprises 20% titanium dioxide masterbatch (containing 60% TiO2, 36% polyester PET, and 4% MAH maleic anhydride grafted SEBS), 0.1% a 1:1 combination of PETG and TPEE, 27% TPX masterbatch (containing 1% Al2O3, 30% TPX, and 69% polyester PET), 0.1% sodium organophosphate, 0.1% polyethylene glycol, and 52.7% polyester (PET). The longitudinal stretch ratio is 3.2, the transverse stretch ratio is 3.8, and the transverse heat setting temperatures in zones 1-5 are 225 / 225 / 225 / 225 / 205°C, respectively. The transition zone temperature is 160°C, and the cooling zone temperatures are 100 / 70°C. The track shrinkage is 2.5%, and the total thickness of the reflective film is 188μm. The relevant performance table is shown in Table 1.

[0045] Example 7 The reflective film's surface layer comprises 1.5% silica, 0.1% PETG, 2% octadecyldimethylhydroxyethyl quaternary ammonium nitrate, and 96.4% polyester (PET), with the aforementioned percentages representing weight percentages of layer A. The reflective film's middle layer comprises 30% titanium dioxide masterbatch (containing 60% TiO2, 36% polyester PET, and 4% MAH maleic anhydride grafted SEBS), 0.1% PETG and TPEE combination (1:1 ratio), 27% TPX masterbatch (containing 1% Al2O3, 30% TPX, and 69% polyester PET), 0.1% sodium organophosphate, 0.1% polyethylene glycol, and 42.7% polyester (PET). The longitudinal stretch ratio is 3.2, the transverse stretch ratio is 3.5, and the transverse heat setting temperatures in zones 1-5 are 225 / 225 / 225 / 225 / 205°C, respectively. The transition zone temperature is 160°C, and the cooling zone temperatures are 100 / 70°C. The track shrinkage is 2.5%, and the total thickness of the reflective film is 188μm. The relevant performance table is shown in Table 1.

[0046] Example 8 The reflective film's surface layer comprises 1.5% silica, 0.1% PETG, 2% octadecyldimethylhydroxyethyl quaternary ammonium nitrate, and 96.4% polyester (PET), with the aforementioned percentages representing weight percentages of layer A. The reflective film's middle layer comprises 10% titanium dioxide masterbatch (containing 60% TiO2, 36% polyester PET, and 4% MAH maleic anhydride grafted SEBS), 0.1% a 1:1 combination of PETG and TPEE, 30% TPX masterbatch (containing 1% Al2O3, 30% TPX, and 69% polyester PET), 0.1% sodium organic phosphate, 0.1% polyethylene glycol, and 59.7% polyester (PET). The longitudinal stretch ratio is 3.4, the transverse stretch ratio is 3.8, and the transverse heat setting temperatures in zones 1-5 are 225 / 225 / 225 / 225 / 205°C, respectively. The transition zone temperature is 160°C, and the cooling zone temperatures are 100 / 70°C. The track shrinkage is 2.5%, and the total thickness of the reflective film is 188μm. The relevant performance table is shown in Table 1.

[0047] Example 9 The reflective film's surface layer comprises 1.5% silica, 0.1% PETG, 2% octadecyldimethylhydroxyethyl quaternary ammonium nitrate, and 96.4% polyester (PET), with the aforementioned percentages representing weight percentages of layer A. The reflective film's middle layer comprises 10% titanium dioxide masterbatch (containing 60% TiO2, 36% polyester PET, and 4% MAH maleic anhydride grafted SEBS), 0.1% a 1:1 combination of PETG and TPEE, 45% TPX masterbatch (containing 1% Al2O3, 30% TPX, and 69% polyester PET), 0.1% sodium organic phosphate, 0.1% polyethylene glycol, and 44.7% polyester (PET). The longitudinal stretch ratio is 3.4, the transverse stretch ratio is 3.6, and the transverse heat setting temperatures in zones 1-5 are 225 / 225 / 225 / 225 / 205°C, respectively. The transition zone temperature is 160°C, and the cooling zone temperatures are 100 / 70°C. The track shrinkage is 2.5%, and the total thickness of the reflective film is 188μm. The relevant performance table is shown in Table 1.

[0048] Example 10 The reflective film's surface layer comprises 1.5% silica, 0.1% PETG, 2% octadecyldimethylhydroxyethyl quaternary ammonium nitrate, and 96.4% polyester (PET), with the aforementioned percentages representing weight percentages of layer A. The reflective film's middle layer comprises 20% titanium dioxide masterbatch (containing 60% TiO2, 36% polyester PET, and 4% MAH maleic anhydride grafted SEBS), 0.1% PETG and TPEE combination (1:1 ratio), 30% TPX masterbatch (containing 1% Al2O3, 30% TPX, and 69% polyester PET), 0.1% sodium organic phosphate, 0.1% polyethylene glycol, and 49.7% polyester (PET). The longitudinal stretch ratio is 3.2, the transverse stretch ratio is 3.6, and the transverse heat setting temperatures in zones 1-5 are 225 / 225 / 225 / 225 / 205°C, respectively. The transition zone temperature is 160°C, and the cooling zone temperatures are 100 / 70°C. The track shrinkage is 2.5%, and the total thickness of the reflective film is 188μm. The relevant performance table is shown in Table 1.

[0049] Example 11 The reflective film's surface layer comprises 1.5% silica, 0.1% PETG, 2% octadecyldimethylhydroxyethyl quaternary ammonium nitrate, and 96.4% polyester (PET), with the aforementioned percentages representing weight percentages of layer A. The reflective film's middle layer comprises 20% titanium dioxide masterbatch (containing 60% TiO2, 36% polyester PET, and 4% MAH maleic anhydride grafted SEBS), 0.1% PETG and TPEE combination (1:1 ratio), 45% TPX masterbatch (containing 1% Al2O3, 30% TPX, and 69% polyester PET), 0.1% sodium organophosphate, 0.1% polyethylene glycol, and 34.7% polyester (PET). The longitudinal stretch ratio is 3.2, the transverse stretch ratio is 3.5, and the transverse heat setting temperatures in zones 1-5 are 225 / 225 / 225 / 225 / 205°C, respectively. The transition zone temperature is 160°C, and the cooling zone temperatures are 100 / 70°C. The track shrinkage is 2.5%, and the total thickness of the reflective film is 188μm. The relevant performance table is shown in Table 1.

[0050] Example 12 The surface layer of the reflective film comprises 1.5% silicon dioxide, 0.1% PETG, 2% octadecyl dimethyl hydroxyethyl quaternary ammonium nitrate, and 96.4% polyester PET. The above percentages are the weight percentages of layer A. The middle layer of the reflective film comprises 10% titanium dioxide masterbatch (containing 60% TiO2, 36% polyester PET, and 4% MAH maleic anhydride grafted SEBS), 0.1% PETG and TPEE combination (ratio of 1:1), 45% TPX masterbatch (containing 1% Al2O3, 30% TPX, and 69% polyester PET), 0.1% sodium organic phosphate, 0.1% polyethylene glycol, and 44.7% polyester PET. The longitudinal stretching ratio is 3.6, the transverse stretching ratio is 3.6, and the temperatures of the transverse stretching heat setting zones 1-5 are respectively 225 / 225 / 225 / 225 / 205℃, the transition zone temperature is 160℃, and the cooling zone temperatures are 100 / 70℃ respectively; the track shrinkage is 2.5%, and the total thickness of the reflective film is 188μm. The relevant performance table is shown in Table 1.

[0051] Example 13 The reflective film's surface layer comprises 1.5% silica, 0.1% PETG, 2% octadecyldimethylhydroxyethyl quaternary ammonium nitrate, and 96.4% polyester (PET), with the aforementioned percentages representing weight percentages of layer A. The reflective film's middle layer comprises 30% titanium dioxide masterbatch (containing 60% TiO2, 36% polyester PET, and 4% MAH maleic anhydride grafted SEBS), 0.1% a 1:1 combination of PETG and TPEE, 30% TPX masterbatch (containing 1% Al2O3, 30% TPX, and 69% polyester PET), 0.1% sodium organic phosphate, 0.1% polyethylene glycol, and 39.7% polyester (PET). The longitudinal stretch ratio is 3.2, the transverse stretch ratio is 3.5, and the transverse heat setting temperatures in zones 1-5 are 225 / 225 / 225 / 225 / 205°C, respectively. The transition zone temperature is 160°C, and the cooling zone temperatures are 100 / 70°C. The track shrinkage is 2.5%, and the total thickness of the reflective film is 188μm. The relevant performance table is shown in Table 1.

[0052] Comparative Example 1 The surface layer of the reflective film comprises 1.5% silicon dioxide, 0.1% PETG, 2% octadecyl dimethyl hydroxyethyl quaternary ammonium nitrate, and 96.4% polyester PET. The above percentages are the weight percentages of layer A. The middle layer of the reflective film comprises 10% titanium dioxide masterbatch (containing 60% TiO2, 36% polyester PET and 4% MAH maleic anhydride grafted SEBS), 0.1% PETG and TPEE combination (ratio of 1:1), 45% TPX (containing 1% Al2O3, 30% TPX and 69% polyester PET), 0.1% sodium organic phosphate, 0.1% polyethylene glycol, 44.7% polyester PET; longitudinal stretching ratio 3.6, transverse stretching ratio 3.4, transverse stretching heat setting zone 1-5 temperature are 225 / 225 / 225 / 225 / 205℃, the transition zone temperature is 160℃, and the cooling zone temperatures are 100 / 70℃ respectively; the track shrinkage is 2.5%, and the total thickness of the reflective film is 188μm. The relevant performance table is shown in Table 1.

[0053] Comparative Example 2 The reflective film's surface layer comprises 1.5% silica, 0.1% PETG, 2% octadecyldimethylhydroxyethyl quaternary ammonium nitrate, and 96.4% polyester (PET), with the aforementioned percentages representing weight percentages of layer A. The reflective film's middle layer comprises 10% titanium dioxide masterbatch (containing 60% TiO2, 36% polyester PET, and 4% MAH maleic anhydride grafted SEBS), 0.1% a 1:1 combination of PETG and TPEE, 30% TPX masterbatch (containing 1% Al2O3, 30% TPX, and 69% polyester PET), 0.1% sodium organic phosphate, 0.1% polyethylene glycol, and 59.7% polyester (PET). The longitudinal stretch ratio is 3.8, the transverse stretch ratio is 3.4, and the transverse heat setting temperatures in zones 1-5 are 225 / 225 / 225 / 225 / 205°C, respectively. The transition zone temperature is 130°C, and the cooling zone temperatures are 80 / 50°C. The track shrinkage is 2.5%, and the total thickness of the reflective film is 188μm. The relevant performance table is shown in Table 1.

[0054] The reflective film prepared by the present invention was tested for performance according to the following method: Reflectivity: Reflectivity was measured in accordance with GB / T3979-2008 using a ColorQuest XE spectrophotometer (Hunterlab) under D65 illuminant using an integrating sphere with a d / 8° configuration. Reflectivity data is the weighted average of the reflectivity at 10nm wavelength intervals from 400-700nm, with the weights corresponding to the energy distribution curve of the D65 illuminant.

[0055] Gloss: Gloss was measured according to GB / T 9754-2007 using a ZGM 1020 60° medium gloss meter. A flat reflective film measuring 3 x 5 cm was selected. Each sample was sampled three times, once on the left, center, and right sides. The instrument was calibrated before testing. After calibration, three films were tested on both sides, recording the data and calculating the average.

[0056] Film surface smoothness: The prepared reflective film is baked according to the baking process temperature, and the prepared reflective film finished roll is passed through the coating guide roller into a four-section oven with a length of 6m per section. The film is baked or coated at a temperature of 90-110°C to verify the film surface flatness. Samples 2m long and 1.2m wide are placed on a marble slab before and after baking. The film surface is observed and recorded.

[0057] Transverse elastic modulus of the film: In accordance with GB / T 25255-2010, an electronic universal testing machine was used to cut the film into strips 10 mm wide (MD) and 150 mm long (TD) along the TD direction. Three strips were taken from each sample for testing. The length of the specimen between the test fixtures was 100 mm. The test tensile speed was 100 mm / s. The slope of the linear portion of the tensile strain curve was calculated to be the elastic modulus of PET. The average of the three sets of data was calculated as the sample ETD.

[0058] Density test: Take 10*10cm size of each sample and place it on the density meter for testing. Take 3 pieces of each sample and record the average value.

[0059] Thickness range test: Take a sample of the finished coil, test the thickness every 50mm along the TD direction, record the results, and finally calculate the thickness range.

[0060] Table 1 Performance of Examples 1-14 and Comparative Examples (188 μm) Serial number <![CDATA[Density g / cm 3 > Film thickness μm Reflectivity% Glossiness GU Film surface before baking Film surface after baking Transverse elastic modulus MPa Finished roll thickness extremes μm Example 1 0.83 188 96.8 58 Smooth without heat wrinkles or waves Smooth without heat wrinkles or waves 2058 7 Example 2 0.90 188 96.5 42 Smooth without heat wrinkles or waves Smooth without heat wrinkles or waves 2046 5 Example 3 0.88 188 96.6 30 Smooth without heat wrinkles or waves Smooth without heat wrinkles or waves 2034 8 Example 4 0.89 188 96.3 21 Smooth without heat wrinkles or waves Smooth without heat wrinkles or waves 1998 6 Example 5 0.88 188 96.9 56 Smooth without heat wrinkles or waves Smooth without heat wrinkles or waves 2000 7 Example 6 0.90 188 97.2 54 Smooth without heat wrinkles or waves Smooth without heat wrinkles or waves 1987 5 Example 7 0.94 188 97.5 52 Smooth without heat wrinkles or waves Smooth without heat wrinkles or waves 1873 6 Example 8 0.76 188 96.7 55 Smooth without heat wrinkles or waves Smooth without heat wrinkles or waves 2006 7 Example 9 0.68 188 97.2 53 Smooth without heat wrinkles or waves Smooth without heat wrinkles or waves 1837 5 Example 10 0.83 188 97.4 57 Smooth without heat wrinkles or waves Smooth without heat wrinkles or waves 1985 5 Example 11 0.80 188 97.6 53 Smooth without heat wrinkles or waves Smooth without heat wrinkles or waves 1943 7 Example 12 0.65 188 97.3 54 Smooth without heat wrinkles or waves Smooth without heat wrinkles or waves 1902 8 Example 13 0.88 188 97.8 53 Smooth without heat wrinkles or waves Smooth without heat wrinkles or waves 1940 6 Comparative Example 1 0.68 188 96.9 53 Smooth, slightly wrinkled, no waves or warping The film surface has obvious heat wrinkles and no wave warping 1750 7 Comparative Example 2 0.75 188 97.1 53 Smooth, slightly wrinkled, slightly wavy The film surface has obvious heat wrinkles and slight waves 1642 8 Refer to the performance parameters in Table 1. It can be seen from Comparative Example 1 that when the longitudinal stretching ratio is higher than the transverse stretching ratio, the flatness of the film surface cannot be improved. In the film-making process of Comparative Example 2, the temperature design of the cooling zone and the transition zone is unreasonable, resulting in slight wrinkles on the film surface, which in turn causes the film surface to be uneven. In the examples, the optical reflective polyester films provided by Examples 6-7, 9-13 have good comprehensive performance, with a reflectivity of ≥97.2. Through reasonable process design, the film surface is flat and free of heat wrinkles. By setting the longitudinal and transverse stretching and heat setting process parameters, the transverse modulus of the film is higher, which improves the film's ability to resist deformation; by setting the temperature from transverse stretching, heat setting to cooling, the internal stress of the film is eliminated, and the film size is not easily changed. Considering the comprehensive cost and reflectivity performance, Example 10 has better performance; the density of Example 9 and Example 12 is relatively low, <0.70g / cm 3 While ensuring reflectivity, it is particularly suitable for subsequent coating and processing applications, offering significant cost-saving advantages. By adjusting the formula, increasing the foaming masterbatch content, and adjusting the process, the present invention reduces the density of the reflective film, lowering the cost per square meter. After coating, the film's stiffness is increased, while overall cost is reduced compared to high-density reflective films.

[0061] The above description is only a preferred embodiment of the present invention and is not intended to limit the scope of protection of the present invention. All equivalent changes and modifications made based on the content of the present invention are included in the patent scope of the present invention.

Claims

1. A reflective film with good surface flatness and high reflectivity, wherein the reflective film is a three-layer structure, including an ABA structure or an ABC structure, and is characterized in that: The intermediate layer of the reflective film includes the following components in weight percentage: Inorganic particles a masterbatch 5-45% Incompatible resin masterbatch 24-45% Nucleating agent 0.1% Toughening agent a 0.1% Dispersant 0.1% Polyester 9.7- 70.7%.

2. The reflective film with good surface flatness and high reflectivity according to claim 1, characterized in that: The incompatible resin masterbatch is obtained by blending and modifying the incompatible resin with Al2O3 particles to form an incompatible resin masterbatch, wherein the incompatible resin masterbatch comprises 30% of incompatible resin, 1% of Al2O3 and 69% of polyester, and the above percentages are weight percentages; the incompatible resin is one or a combination of two of polymethylpentene (TPX), styrene, polypropylene, polyurethane resin and polycarbonate resin.

3. The reflective film with good surface flatness and high reflectivity according to claim 1, characterized in that: The inorganic particle a masterbatch is prepared by grafting and modifying the inorganic particle a with MAH maleic anhydride grafted SEBS model (FG1901) to form a masterbatch, which includes 60% of inorganic particle a, 4% of MAH maleic anhydride grafted SEBS and 36% of polyester, and the inorganic particle a includes one or two of barium sulfate, titanium dioxide and aluminum oxide.

4. The reflective film with good surface flatness and high reflectivity according to claim 1, characterized in that: The reflective film is preferably an ABA structure, and the surface layer includes the following components in percentage by weight: Inorganic particles b 1~3%; Toughening agent b 0.1%; Antistatic agent 2%; Polyester 94.9~96.9%.

5. The reflective film with good surface flatness and high reflectivity according to claim 4, characterized in that: The inorganic particles b include one or a combination of two of silicon dioxide, titanium dioxide, calcium carbonate, and aluminum oxide.

6. The reflective film with good surface flatness and high reflectivity according to claim 4, characterized in that: The toughening agent a contained in the middle layer of the reflective film is a non-crystalline polyester, preferably a combination of PETG:TPEE, with a ratio of 1:1; the nucleating agent can be an inorganic nucleating agent or an organic nucleating agent, the inorganic nucleating agent includes metal oxides, inorganic salts or clays, and the inorganic nucleating agent includes organic sodium salts or aromatic hydroxysulfonates; the nucleating agent is preferably organic sodium phosphate; the dispersant is preferably polyethylene glycol; the toughening agent b contained in the surface layer of the reflective film is a non-crystalline polyester; the antistatic agent is octadecyl dimethyl hydroxyethyl quaternary ammonium nitrate.

7. The reflective film with good surface flatness and high reflectivity according to claims 2, 3 and 4, characterized in that: The polyester includes one or two of polyethylene terephthalate (PET), polybutylene terephthalate (PBT), and polyethylene naphthalate.

8. The reflective film with good surface flatness and high reflectivity according to claim 7, characterized in that: When the polyester in the middle layer is PET, the incompatible resin is polymethylpentene, and its melt index MFR satisfies 100≤MFR (260°C, 5kg)≤180g / min.

9. A method for preparing a reflective film with good surface flatness and high reflectivity as claimed in any one of claims 1 to 8, characterized in that: The preparation method comprises the following steps: S1, casting: adopting a three-layer co-extrusion process; the PET polyester chips, antistatic agent, inorganic particles b and toughening agent b in the surface layer are melted and extruded, and then introduced into the T-die mouth through a filter; at the same time, the PET polyester chips, inorganic particle a masterbatch, incompatible resin masterbatch, nucleating agent, toughening agent a and dispersant in the middle layer are melted and extruded, and then introduced into the T-die mouth through a filter; then three-layer co-extrusion is performed, and the molten sheet is cooled by a cold roller to obtain a casting sheet; S2, stretching film forming: the cast sheet obtained in step S1 is first preheated by longitudinal stretching rollers, and then longitudinally stretched under the auxiliary heating of infrared lamps. The longitudinal stretching ratio (L MD ) is 3.0-3.7, and a single-stretch membrane is obtained; the membrane is introduced into the clamps on both sides of the horizontal stretching entrance and clamped, and then enters the horizontal stretching system. The horizontal stretching ratio (L TD ) is 3.2~4.

0. After heat setting and cooling, the edges are trimmed in the traction area, and then rolled, slit and packaged to obtain the reflective film.

10. The method for preparing a reflective film with good surface flatness and high reflectivity according to claim 9, characterized in that: In step S2, 1.0≤L TD / L MD ≤1.33; total thickness of reflective film is 50-300μm, density of reflective film is 0.65~0.95g / cm 3 .

Citation Information

Patent Citations

  • White reflective polyester film and preparation method thereof

    CN104608446A

  • Preparation method of low-thermal-shrinkage polyester polyester reflective film

    CN106671544A

  • Optical reflective film and preparation method thereof

    CN106908864A

  • Non-coating type diffuse reflection film and manufacturing method thereof

    CN106908882A

  • High-gloss white reflective polyester film

    CN112297553A